6LoWPAN based smart home architecture for the smart future - Hasan, Shah Muhammad Jannatul; Ali, Mohammad; Khan, Taufiqul Islam; Afrin, Farzana (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.